Earthquakes, communities and heritage: Telling stories of resilience through co-designed immersive media. Issue 1 (1st January 2023) - Galeazzi, Fabrizio; Di Franco, Paola Di Giuseppantonio; Toulson, Rob; Camporesi, Carlo; Patel, Shreepali
Abstract : In this article, we discuss the experimental application of iterative co-design, community-based and place-centred approaches in the creation of 3D immersive experiences of places that have been badly damaged or destroyed after natural catastrophic events. We take as our case study the community of Senerchia, hit and partially destroyed by the 1980 Irpinia earthquake in Italy. The main purpose of this paper is to analyse and discuss the co-creation process we undertook with residents of the town for the making of an immersive documentary Italia Terremotata which explores life before, during and after the earthquake. Our approach is based on design-thinking and aims to define an ethical framework for the creation of reflexive and multi-vocal 3D immersive storytelling systems that consider 'vulnerability' and 'empathy' as central design values of the iterative prototyping and co-creation cycle.